IMPLEMENTATION OF ONLINE BANKING USING SOAP - G. , Sai Prudhvi Raj; A., Sivanesh kumar (International Journal of Psychosocial Rehabilitation, 2020)
This current scenario computing technology is used in various fields like data collection, data processing, data retrieval, data storage, etc. Computing power is also used in the banking field. The entire banking activity of modern banks is controlled by computers. Online banking allows the users to access their bank accounts and make any transactions without visiting the branches of the financial institutes. Online banking is also called internet banking or web banking. Online banking provides many favors to the users. This is an electronic payment system that allows customers of the bank or financial institutes to conduct transactions through the financial institute’s website. SOAP is a particular protocol for performing RPC. RPC refers to remote procedure calling. Soap is a messaging protocol specification for transferring structural data in the implementation on the web service in the computer. Soap refers to the simple object access protocol, which is an internet protocol Banking is full of stricts because of security reasons. Here Soap is implementation on the online banking for better security.